Composition, Clinical Efficiency, and Mechanism of NHC-Approved “Three Chinese Medicines and Three Chinese Recipes” for COVID-19 Treatment - Xia, Ke-Yao; Zhao, Zeyuan; Shah, Taif; Wang, Jing-Yi; Baloch, Zulqarnain (Frontiers in Pharmacology, 2022)
Traditional Chinese Medicines (TCMs) have been regularly prescribed to treat and prevent diseases for thousands of years in the eastern part of the Asian continent. Thus, when the COVID-19 epidemic started, TCM was officially incorporated as a strategy by the NHC for the treatment of COVID-19 infection. TCMs were used to treat COVID-19 and had a significant effect on alleviating symptoms, delaying disease progression, improving the cure rate, and reducing the mortality rate in China. Therefore, China's national health commission officially approved Qingfei Paidu decoction, Xuanfei Baidu decoction, Huashi Baidu decoction, Lianhua Qingwen capsules, Jinhua Qinggan granules, and Xuebijing for the COVID-19 treatment. This review evaluates and summarizes the use of TCMs against infectious diseases and the composition, clinical efficacy, and mechanisms of the NHC-approved “three Chinese medicines and three Chinese recipes” for COVID-19 treatment. “Three Chinese medicines and three Chinese recipes” have been demonstrated to be highly effective against COVID-19, but there is a lack of in vivo or in vitro evidence. Most of the available data related to the potential mechanism of “three Chinese medicines and three Chinese recipes” is based on virtual simulation or prediction, which is acquired via molecular docking and network pharmacology analysis. These predictions have not yet been proven. Therefore, there is a need for high-quality in vivo and in vitro, and clinical studies by employing new strategies and technologies such as genomics, metabolomics, and proteomics to verify the predicted mechanisms of these drug's effects on COVID-19.